1979
DOI: 10.1159/000194053
|View full text |Cite
|
Sign up to set email alerts
|

Donor- and Organ-Specific Evaluation of Antibodies Eluted from Canine Lung Allografts Rejected by Immunosuppressively Treated and Untreated Recipients

Abstract: Using elution techniques, the humoral lung allograft rejection in immunosuppressively treated versus untreated recipients is analyzed at the donor organ specific level. The antibodies were evaluated quantitatively and qualitatively by elution of lung graft bound immunoglobulins and by testing the eluates against donor lung antigen using passive hemagglutination and indirect immunofluorescence. By correlating the results in those assays, a considerable amount of humoral anti-donor lung antibodies could by prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Our study demonstrated a correlation between the development of antibodies (Abs) to donor mismatched HLA (DSA) during post-transplantation and the risk for BOS (4). Furthermore, Abs against HLA has been eluted from lungs that underwent chronic rejection (5). Further support for the possible role for anti-HLA in the immunopathogenesis of obliterative airway disease (OAD) has been provided by studies in which administration of anti-HLA class I intra-bronchially into produced OAD in the native lungs (6).…”
Section: Introductionmentioning
confidence: 99%
“…Our study demonstrated a correlation between the development of antibodies (Abs) to donor mismatched HLA (DSA) during post-transplantation and the risk for BOS (4). Furthermore, Abs against HLA has been eluted from lungs that underwent chronic rejection (5). Further support for the possible role for anti-HLA in the immunopathogenesis of obliterative airway disease (OAD) has been provided by studies in which administration of anti-HLA class I intra-bronchially into produced OAD in the native lungs (6).…”
Section: Introductionmentioning
confidence: 99%